The Work of Maternity and Infant Welfare Centres - Labour Party (Great Britain). Advisory Committee on Public Health
1926-01 1926 1920s 7 pages - 5 - (121b) wasting and respiratory diseases are often directly caused by poverty and poor surroundings with their evil of over-crowding and lack of fresh air. Two conclusions must therefore be drawn:- (1) That Ante-Natal and Maternity work must be greatly increased, and (2) That Infant Welfare from being a Medical problem is becoming more and more a social problem and must take into consideration not only the education of the mother, but her environment. Of the 2,112 Centres, only 356, unfortunately, have separate Ante-Natal Clinics though most of them do some ante-natal work with the infant work. The maternal mortality has practically remained unchanged for the last 20 years and there is a loss of about 3,000 mothers annually. This may not strike the imagination as being high, but there is in addition an amount of suffering and damage consequent on child-bearing which cannot be estimated in figures, and which should be prevented. In some rural districts - notably in Wales, - and in the industrial and mining centres of the North, the maternal death-rate is the heaviest. Sometimes general conditions are at fault in lowering the vitality of the working mother:- bad housing, imperfect drainage and water supply, under-feeding and overwork, and insufficient rest before and after confinement. The heavy drudgery of the home is responsible for much mischief, unless the mother is wonderfully strong. The high mortality rate in mining districts may be partly due to the excessive hard work of the mother in the home, in washing dirty clothes and spending hours at the wash-tub. One-third of the deaths, however, are from sepsis, pointing to a greater need of aseptic cleanliness. The "Handy woman" should be abolished, the supply of midwives increased and the Medical Schools should insist on a higher standard of midwifery and gynaecological training. There is already, - since January 1923, - some improvement in this last. 292/824/1/135